Novice Researcher Experiences in Publishing Article A Study at English Education Department UINSA - Rahmasari, Annisa; Salik, Mohamad; Soraya, Irma (Department of English Language Education, UIN Sunan Ampel Surabaya, 2024)
Students on the undergraduate level known as novice researchers are expected to have experiences in research and publication during their study. As novice researchers, English education students are also expected to participate in research projects and write research articles for publication. This study aimed to explore novice researchers' experiences in research and publication related to the motivation and challenges among English education department students of UINSA. This study is a qualitative study that used questionnaire and interview guidelines as the research instrument to gather data from 17 students of English education department who has submit their article to journal. The findings of this study are; (1) Students are motivated to work on research and publication to completing assessed coursework during their study, gaining new knowledge and fulfilling their personal satisfaction. (2) The challenges students faced during the research and publication are finding the references that related to their study, collecting the data, presenting the result into a research article. Additionally, during the publication waiting process becomes a challenge that most of the students face. From the findings it can be conclude that most of the English education department students UINSA motivated to participate in research and publication to complete a specific course during their study. However, only few of the students who submit their article for publication because they faced varied challenges in the process of publication such as the waiting and revision process.